Simultaneous automatic insufﬂation and smoke-evacuation system in flexible gastrointestinal endoscopy - Takahashi, Hidekazu; Hirota, Masashi; Takahashi, Tsuyoshi; Yamasaki, Makoto; Miyazaki, Yasuhiro; Makino, Tomoki; Kurokawa, Yukinori; Takiguchi, Shuji; Mori, Masaki; Doki, Yuichiro; Nakajima, Kiyokazu (Endoscopy, 2016)
Background and aims: Automatic smoke evacuation has not been feasible inside the gastrointestinal tract as evacuation collapses pneumoviscera. As previously reported, steady pressure automatically controlled endoscopy (SPACE) may resolve this problem. The aims of this study were to clarify the potential dangers of surgical smoke, and to evaluate the feasibility and potential usefulness of automatic smoke evacuation in flexible gastrointestinal endoscopy.Methods: Seven pigs were enrolled. SPACE was established by using a flexible endoscope, an overtube, and a surgical CO2 insufflator. Smoke was generated by gastric mucosal ablation for component analysis and was evacuated by a commercially available surgical-use smoke evacuator connected to an additional line attached to the endoscope. Endoscopic images with evacuation were evaluated subjectively in comparison to those from cases without evacuation. After each session, the residual intraluminal smoke was collected by a smoke testing device for objective evaluation.Results: Ten chemical compounds were detected. Smoke evacuation was achieved without collapse of the pneumostomach. Smoke was significantly reduced with the use of evacuation.Conclusions: Surgical smoke generated inside the gut lumen was potentially hazardous. Automatic evacuation was feasible and potentially useful in conjunction with SPACE technology.